PENGEMBANGAN DAN APLIKASI PEMBELAJARAN PAI DI SD - Nandang Kosim (QATHRUNÂ, 2015)
Islamic education is part of the National Education and has an important position in the National Education system. Because of Islamic education is very important, then the learning process of Islamic Education in Primary Schools is necessary the development and application of appropriate learning, focused and integrated.The most appropriate learning development for Islamic education is through contextual learning approach (Contextual Teacing and Learning/CTL). As for applying the learning there are four aspects that must be considered in the application of learning strategies include 1) learning activities, 2) learning methods, 3) instructional media and 4) time spent in completing each step teacher learning activities.